Bioinformatics: An Application of Data Mining - Yamini, O; Ramakrishna, S (International Journal of Computer Sciences and Engineering, 2025)
One of the foremost active areas of inferring structure and principles of biological datasets is that the use of knowledge mining to resolve biological issues. Some typical samples of biological analysis performed by data processing involve supermolecule structure prediction; cistron Classification, analysis of mutations in cancer and cistron expressions. Over recent years the studies in proteomic, genetics Associate in Nursing the varied different biological researches has generated a progressively great deal of biological knowledge. Drawing conclusions from this knowledge needs subtle machine analysis so as to interpret the information. As biological data and research become ever vaster, it is important that the application of data mining progresses in order to continue the development of an active area of research within Bioinformatics. This aims to draw information from varied academic sources in order to discuss an overview of data mining, Bioinformatics, the application of data mining in Bioinformatics and a conclusive summary.